Designing of Robot Gamelan Music using ATmega 16 Microcontroller - Handri Jir Azhar; Ferry Hadary; Syaifurrahman Syaifurrahman (Institute of Advanced Engineering and Science, 2017)
This paper presents a robot concept which is the robot can play the instrumental Gamelan music. Gamelan is a percussive instrument. Instrumental Gamelan music keys are consist of 2 octaves in 15 tones. Robot Gamelan music is using proportional-derivative (PD) control system. PD control of the robot is by controlling DC gear motor position to desired Gamelan key position. Robot Gamelan music using ATmega 16 microcontroller as a controller. Feedback of PD control is using magnetic rotary encoder (MRE) sensor. PD control is using the constant. The constant functions of PD control are determining the pulse width modulation (PWM) toward DC gear motor velocity in order to reposition a gamelan key position and pushing down the errors.